Imam Shawkani: taqlid's foe, ijtihad's friend - Ali, Mohammed Farid (IAIS Malaysia, 2013)
Imam Shawkani is Muhammad b. Ali b. Muhammad b. Abdillah al-Shawkani al-Sanani (born 1760). He is called al-Shawkani because of his attribution to his birth place, Hijrah Shawkan a small town a day’s journey from Sana, Yemen. He is also known as al-Sanani as an attribution to Sana where he grew up, studied and held the position of Qadi al-qudat under the Qasimi Imam rulers. In his early years, he studied under his father Ali b. Muhammad al-Shawkani (d. 1797) who was a judge of Sana. It is difficult to say whether al-Shawkani was a Zaydi or Sunni, but his milieu was Zaydi. He was well read, educated in both the Zaydi and the Sunni traditions...........